AI am Motivated: Leveraging Self-Determination Theory in Chatbots - Craig Sims; Jack Moursounidis; Rachel Sheffield; Nik Thompson; Abhijeet Singh; Anna Bunn; Li Sha (Tecno Scientifica Publisher, 2026)
Artificial intelligence (AI)-powered chatbots promised to streamline administrative tasks and offer just-in-time support within higher education institutions. However, many existing chatbots prioritised simple information delivery over the cultivation of deeper student engagement and intrinsic motivation. This paper argued that Self-Determination Theory (SDT), a prominent framework for understanding motivation, offered a robust model for designing chatbots that went beyond passive answering to become active facilitators of student agency. SDT emphasised three core psychological needs: autonomy, competence, and relatedness. This paper explored how the intentional integration of these needs into chatbot design could transform administrative support interactions into opportunities to empower students as self-directed learners.